Exploring Lyophilised Suillus granulatus Extracts as Natural Additives for Industrially Produced Functional Dehydrated Soups - Monika Stojanova; Milena Pantic; Anita Klaus; Dunja Miletic; Dragana Mihajlovic; Marina T. Stojanova; Blazo Boev; Miomir Niksic (Flavour and Fragrance Journal, Wiley, 2025)
This study focused on creating lyophilised extracts from Suillus granulatus to assess its antimicrobial properties and explore its potential as a natural substitute for monosodium glutamate in dehydrated soups. The water extract demonstrated stronger antimicrobial activity against L. ivanovii than chloramphenicol. The MBC and MFC values for the water extract were significantly lower (p < 0.05) against L. ivanovii (5.0 mg mL−1), E. faecalis (10 mg mL−1), S. enteritidis (20.0 mg mL−1) and C. neoformans (2.5 mg mL−1) compared to the ethanol extract. Both extracts were more effective against Gram-negative bacteria. Scanning electron microscopy revealed a rough structure in the water extract and a granular structure in the ethanol extract. FT-IR analysis of the mushroom extracts reveals that the carbohydrate subregion is primarily influenced by glucan vibrations, as glucans represent the dominant polysaccharides in mushrooms. The characteristic absorption bands at 1160 cm−1 (appearing as a shoulder), 1078, 1048 and 908 cm−1 correspond to β-D-glucan, while the bands observed at 1148, 1027 and 937 cm−1 indicate the presence of α-D-glucan. The lyophilised water extract exhibited better activity against E. faecalis than the ethanol extract. These findings support the creation of healthier, safer products, encouraging long-term health benefits through daily consumption. This study points to a promising future for the development of functional, high-quality and safe food products by replacing synthetic additives, such as MSG, with natural, antimicrobial-rich mushroom extracts. Ultimately, Suillus granulatus could play a pivotal role in advancing the industrial production of functional foods. Further studies, including in vivo testing, will be conducted.